Single-cell RNA sequencing reveals the dynamics and heterogeneity of lymph node immune cells during acute and chronic viral infections - Jin, Yubei; He, Yudan; Liu, Bing; Zhang, Xiaohui; Song, Caimei; Wu, Yunchen; Hu, Wenjing; Yan, Yiwen; Chen, Nuo; Ding, Yingying; Ou, Yuanyuan; Wu, Yixiu; et al. (Frontiers in Immunology, 2024)
The host immune response determines the differential outcome of acute or chronic viral infections. The comprehensive comparison of lymphoid tissue immune cells at the single-cell level between acute and chronic viral infections is largely insufficient. To explore the landscape of immune responses to acute and chronic viral infections, singlecell RNA sequencing(scRNA-seq), scTCR-seq and scBCR-seq were utilized to evaluate the longitudinal dynamics and heterogeneity of lymph node CD45 + immune cells in mouse models of acute (LCMV Armstrong) and chronic (LCMV clone 13) viral infections. In contrast with acute viral infection, chronic viral infection distinctly induced more robust NK cells and plasma cells at the early stage (Day 4 post-infection) and acute stage (Day 8 post-infection), respectively. Moreover, chronic viral infection exerted decreased but aberrantly activated plasmacytoid dendritic cells (pDCs) at the acute phase. Simultaneously, there were significantly increased IgA + plasma cells (MALT B cells) but differential usage of B-cell receptors in chronic infection. In terms of T-cell responses, Gzma-high effector-like CD8 + T cells were significantly induced at the early stage in chronic infection, which showed temporally reversed gene expression throughout viral infection and the differential usage of the most dominant TCR clonotype. Chronic infection also induced more robust CD4 + T cell responses, including follicular helper T cells (Tfh) and regulatory T cells (Treg). In addition, chronic infection compromised the TCR diversity in both CD8 + and CD4 + T cells. In conclusion, gene expression and TCR/BCR immune repertoire profiling at the singlecell level in this study provide new insights into the dynamic and differential immune responses to acute and chronic viral infections.